Service Engineering Based on Service Oriented Architecture Methodology - Suhardi Suhardi; Robin Doss; Purnomo Yustianto (Universitas Ahmad Dahlan, 2015)
Service Engineering (SE) and Service Oriented Architecture (SOA) originally reside on different plateaus of discipline. SE is defined as a set of activity introducing a new business service, while SOA is a technical approach to redefine an enterprise business processes as a set of IT enabled services. This paper proposes a SOA embedded SE framework as a comprehensive approach in re-defining business service and its IT implementation. After an introduction, a review of existing SE frameworks and SOA methodologies is presented in the paper. Afterward, a complete SE framework is proposed with several results on early case studies. A survey results are then presented to prove the usability and benefit of the proposed framework. The framework is designed and proposed to help practitioners and researchers to conduct service engineering by employing principles and methodology offered by SOA approach.